Iddah Wafat, Antara Agama Dan Budaya (Studi Kasus Iddah Wafat Di Kecamatan Sangkapura) - Arsjad, Rasyida; Barakah, Ainun (STAI Miftahul Ula Nganjuk, 2017)
Abstract: Islam always respect the dignity of a woman when being a wife and a mother when she relates in the marriage. Mutaddah woman (wife who left for dead by her husband) has prescribed period for four (4) months and ten (10) days, during which a woman must wait to not accept the (marriage) proposal and married, but must carry out the obligations and prohibitions, called the ihdad as a tribute to her husband. As for the wisdom of in infected the Iddah is to determine the void womb of a woman in keeping her nasab (descent) and her purity. Sometimes customs and culture affects a law even urf (customs) tends to be a role model. It is understood they are due commonness of a person in a nash (postulate) so it is effected to tasahul (oversimplify) in the implementation of worship and muamalah. The methodology research is used field research (case studies in the field), using a qualitative descriptive approach. However, negligence is still in the corridors of shariah, it means that most of them do not do ihdad (obligations and prohibitions) while doing his Iddah. It takes a real solution to fix and straighten understanding. Through individual approach, religious activities, the involvement of government officials, especially the Religious Courts (PA) and the Religious Affairs Office (KUA) who involved in family law issues directly; marriage, divorce and other cases.